THE RELATIONSHIP OF ADOLESCENT WOMEN'S KNOWLEDGE ABOUT MENSTRUATION WITH READINESS TO FACE MENARCHE AT MTS NURUL IMAN At SIMPANG EMPAT KABUPATEN ASAHAN - Lukita Pratiwi; Mutiara Dwi Yanti (BEST Journal (Biology Education, Sains and Technology), 2023)
Background, Menarche is the first menstruation that usually occurs in a span of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. Menarche usually occurs between three to eight days, but an average of five days. Menstruation is regular bleeding from the uterus as a sign that the uterus is functioning properly. The purpose, of  this study was to determine the correlation between knowledge of menstruation and the readliness of  menarche on female adolescents at MTs Nurul Iman Asahan. This Reaserch used the design of correlational reaserch with cross sectional study approach. Samples, class VII young women as many as 40 people, the instrument used in the form of a questionnaire consisting of 25 statements. Data analysis techniques using Chi-Square. Research Results, the majority of less knowledgeable as many as 24 people (60%) and a well-informed minority of 6 people (15%). Conclusions, there is a significant relationship between knowledge and readiness to face menarche in MTs Nurul Iman Simpang Empat Asahan in2022 students who are seen from the results of the p-value of 0.032 α 0.05. Suggestions, young women can better prepare themselves with important information related to menstruation to increase knowledge.